Bacillus cereus Enhanced Medicinal Ingredient Biosynthesis in Glycyrrhiza uralensis Fisch. Under Different Conditions Based on the Transcriptome and Polymerase Chain Reaction Analysis - Zhang, Yu; Lang, Duoyong; Zhang, Wenjin; Zhang, Xinhui (Frontiers in Plant Science, 2022)
The aim of this study is to evaluate the effects of B. cereus on the seedling growth and accumulation of medicinal ingredients of G. uralensis under control and salt stress conditions. Our results revealed that the different regulatory mechanisms of B. cereus on the seedling growth and accumulation of medicinal ingredients particularly in different conditions based on the transcriptome and PCR analysis. Under control conditions, B. cereus significantly increased the expression of the β-AS, SQS, CHS, LUS, UGAT, CYP72A154 and CYP88D6 genes and liquiritigenin content. Under salt stress, B. cereus significantly increased root length and lateral root number of G. uralensis seedlings, the expression of HMGR, β-AS, CHS, LUS, UGAT, CYP72A154, CYP88D6 and SE genes, and the contents of glycyrrhizic acid and glycyrrhetinic acid. Notably, the effects of B. cereus on the seedlings growth and the secondary metabolites synthesis pathway were different under control and salt stress conditions. Obviously, the effect of B. cereus on the seedling growth under salt stress was better than that under control condition. Moreover, B. cereus increased liquiritigenin content under control condition is closely related to regulate flavone and flavonol biosynthesis, and increased glycyrrhizic acid and glycyrrhetinic acid contents under salt stress condition is closely related to regulate phenylpropanoid biosynthesis, and MVA pathway is also involved. All in all, endophytes B. cereus could be used as sustainable tool to develop effective bioinoculants to enhance the secondary metabolite contents in G. uralensis.